2010
DOI: 10.1111/j.1439-0396.2008.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive evaluation of legume seeds for ruminant feeding

Abstract: Chemical composition, rumen degradability and the effect of particle losses, and intestinal digestibility of protein by using in situ-in vitro and in vitro techniques were stated for beans (Vicia faba), lupin (Lupinus albus), vetch (Vicia sativa) and bitter vetch (Vicia ervilia) and four diets including those legume seeds. In addition, the apparent digestibility of experimental diets was determined in goats. The legume seeds showed high protein content (206-319 g/kg dry matter). Effective degradability of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
(79 reference statements)
4
24
1
2
Order By: Relevance
“…Despite the decrease in the "A" fraction in the extruded peas, the ED of the peas did not present any differences as a result of extrusion (P>0.05). Extrusion reduced the solubility and the fractional degradation rate in the lupin, which was also observed by Rémond et al (2003) and Ramos-Morales et al (2010). In this study, the ED obtained in lupins was lower than that in the abovementioned works, which may be attributed to the use of dehulled lupin instead of whole grain.…”
Section: Crude Protein Degradation Kineticssupporting
confidence: 63%
“…Despite the decrease in the "A" fraction in the extruded peas, the ED of the peas did not present any differences as a result of extrusion (P>0.05). Extrusion reduced the solubility and the fractional degradation rate in the lupin, which was also observed by Rémond et al (2003) and Ramos-Morales et al (2010). In this study, the ED obtained in lupins was lower than that in the abovementioned works, which may be attributed to the use of dehulled lupin instead of whole grain.…”
Section: Crude Protein Degradation Kineticssupporting
confidence: 63%
“…Ipharraguerre and Clark (2005) pointed out that the supply of microbial protein could be balanced by using protein sources that are resistant to ruminal degradation. The animal would thus acquire an additional supply of N. In a previous study the degradability of the crude protein of each legume seed was analysed (Ramos Morales et al., 2008b). Taking into account the soluble fraction (40.7, 51.9, 42.0 and 38.7% for L, FB, BV and V, respectively) and overall the effective degradability values (87.5, 86.2, 82,4 and 79.8% for L, FB, BV and V, respectively), the legumes used may be considered as a source of degradable protein for ruminal micro‐organisms and, therefore, for microbial protein synthesis (González and Andrés, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We believe the tannin content might determine the degradability of the dry matter or of the crude protein in each legume supplied. Comparison of the effective degradability of the protein in each legume with its tannin content (Ramos Morales et al, 2008b) showed that there is no relation between these values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water solubility (WS) of DM and CP was estimated in the filter test according to the procedure described by Ramos-Morales et al (2010).…”
Section: In Sacco Degradability Studiesmentioning
confidence: 99%